Determinants of artificial intelligence use in research at higher learning institutions of Tanzania - Mbilinyi, Augustino Peter; Mwalukasa, Nicholous; Mahenge, Michael (African Quarterly Social Science Review, 2025)
Paper submitted to the Journal of African Quarterly Social Science Review